How to overcome the Great Financial Crisis: An asset exchange approach - Ulrich van Suntum (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2009)
The reasons for the current financial crisis are analysed and a proposal for financing a bad bank is made. In particular, it is proposed to give the banks in trouble government zero bonds rather than cash in exchange for their toxic assets. The term of the zero bonds is determined individually according to the effective failure ratio of the toxic assets. As the latter is yet unknown, this procedure avoids the problem of evaluating them in advance and at the same time ensures that the entire costs of adjustments are lastly borne by the banks themselves rather than by the taxpayer. This solution is suitable for all but the worst cases, where insolvency is inevitable. It is argued that a similar asset exchange approach has already proved to work two times in German History, and that there is no reason to fear that it could hamper the effectiveness of financial markets in future.
Keywords: 330